Student errors in solving HOTS based-match story problems with Newman's theory - Indah Badriani; Andi Fajeriani Wyrasti; Benidiktus Tanujaya (Jurnal Elemen, 2022)
Students' ability for HOTS is critical to acquire. However, the PISA survey in 2018 showed that Indonesian participants were at level 1, and the national exam in 2018 indicated that 40% of students had an issue answering HOTS questions. The problem suggests that students solve questions requiring higher-order thinking skills, causing errors. Therefore, the study aimed to analyze student errors based on Newman's Theory in solving HOTS-based math story problems. The method applied for qualitative research with a descriptive approach. Data collection involved 126 grade IX students using HOTS-based math story tests, interviews, and documentation. Students were grouped into three categories from the HOTS-based math story test results: students with good, medium, and low abilities. This step was to find the average and standard deviation of the scores obtained by respondents when completing the given test. Then three students were selected from each category as subjects. The results showed that as many as 50% of students misunderstood the questions, 20% made transformation errors, and 10% errors in reading, processing skills, and encoding. The high error rate of these students shows the poor ability of students to solve HOTS-based math story problems.